Pink October 2023 celebration in Hospital Al-Sultan Abdullah - Abdul Rashid, Nor Faezan; Abdullah, Muhammad Safwan; Osman, Nora Julianna; Othman, Suraya; Ramli Hamid, Marlina Tanty; Hasbullah, Harissa Husainy (Faculty of Medicine, 2023)
On 4th October 2023, the Department of Surgery, in collaboration with the Department of Radiology and Oncology Unit had organized our yearly Pink October event in Hospital Al-Sultan Abdullah (HASA). The event was officiated by the hospital director, Prof. Dr. Sazzli Shahlan Kasim. The main purpose of the Pink October campaign was to create awareness on Breast Cancer, as October is a dedicated month for breast cancer awareness worldwide